Past performance and current status of agricultural and rural development in Vietnam: Viet Nam Agricultural Sector Program ADB TA 3223-VIE: Phase I Technical Report - Goletti, Francesco (International Food Policy Research Institute, 2000)
This document is the inception report for an ADB-funded TA on Agricultural Sector Program. The overall objective of the TA is to assist the government in designing an agricultural program to help establish a competitive market-based and diversified system through policy reforms in several critical areas and subsectors. The specific objectives of the TA are: i) to assess the impact of previous policy changes in the sector and the current status of agricultural strategies and plans; ii) to conduct detailed analysis and provide recommendations for future policy and institutional changes; and iii) to prepare draft strategies for the sector for the next 5, 10 and 20 years, and a proposal for an agricultural development program. This report is organized into five chapters, including the introduction (chapter 1). Chapter 2 reviews the past performance and current status of the agricultural sector. The chapter stresses the achievements of the past 10 years, after Resolution No. 10 recognized the household as an autonomous economic agent, setting in motion impressive agricultural growth. The chapter reviews progress in production, market orientation and poverty reduction. It also highlights the shift of emphasis from agricultural production to rural development. Chapter 3 discusses the main constraints to accelerating growth in a sustainable and equitable manner. It provides a conceptual framework that stresses the agrarian and rural structure of Vietnamese society and the implications for analysis of constraints. Constraints are classified into three time periods: short term (5 years), medium term (10 years), and long term (more than 10 years). Chapter 4 gives an overview of several global changes that will affect future sectoral performance. Together with the analysis of past performance, current status, and constraints carried out in the previous chapters, this allows identification of the major issues facing agriculture in Viet Nam. Chapter 5 reviews the Asian Development Bank funded Agricultural Sector Program carried out between 1995 and 1998. It examines the loan agreement and the program's impact on income and poverty, as well as the impact of the technical assistance projects on rice and land.